PETS AS THERAPY: THE ROLE OF CATS AND DOGS IN REDUCING STRESS AND BLOOD PRESSURE - Indratiawati, Indratiawati; Setyawan, Yuswanto (LPPM Univ. Ibn Khaldun Bogor, 2025)
Pet ownership, particularly of cats and dogs, has been increasingly recognized as contributing to human health and well-being. Globally, cardiovascular disease and stress-related disorders remain significant health burdens, including in Indonesia where the prevalence of hypertension continues to rise. This study analyzed the relationship between keeping cats and dogs with stress reduction and blood pressure levels among 150 adult respondents in Sidoarjo using chi-square and Spearman correlation tests. The findings demonstrated that individuals who owned or interacted regularly with pets showed significantly lower levels of stress and better cardiovascular responses compared to those without pets. This suggests that cats and dogs can play a complementary role in community-based health promotion strategies by providing natural, non-pharmacological support to mental and physical health. The results further highlight the potential integration of animal-assisted approaches in public health programs, emphasizing their accessibility and sustainability. Future research is encouraged to explore long-term impacts and differences across demographic groups to strengthen the application of pet-assisted health interventions.